Local Government Capacity in Transmigration Development, Indonesia - Isra Muksin (Ilomata International Journal of Social Science, 2023)
The aims of this study were to explore the capacity of local governments in developing transmigration areas in the decentralization era after the change in the transmigration paradigm from migration of the poor to the development of transmigration areas. This research uses a constructive qualitative case study approach. Data collection was done by means of in-depth interviews with 35 participants from echelon two and echelon three officials in Kota Tidore Kepulauan, echelon three in the provincial government and echelons three and four in the central ministry. Our research exposes that the capacity of the local government of Kota Tidore Kepulauan in developing the transmigration area has not been maximized due to unhealthy local political dynamics because each change of regional head can affect the transfer and rotation of positions, the lack of funding sources so that the dependence on the budget from the central government is very high. In addition, cross-sectoral coordination did not go well because each agency still had sectoral ego even though transmigration affairs were not only the task of the transmigration technical service but were the affairs of the local government. Even, human resource support is still very limited, while the procurement of ASN (State Civil Apparatus) must obtain approval from the central government, so local governments are experiencing difficultiesThe aims of this study were to explore the capacity of local governments in developing transmigration areas in the decentralization era after the change in the transmigration paradigm from migration of the poor to the development of transmigration areas. This research uses a constructive qualitative case study approach. Data collection was done by means of in-depth interviews with 35 participants from echelon two and echelon three officials in Kota Tidore Kepulauan, echelon three in the provincial government and echelons three and four in the central ministry. Our research exposes that the capacity of the local government of Kota Tidore Kepulauan in developing the transmigration area has not been maximized due to unhealthy local political dynamics because each change of regional head can affect the transfer and rotation of positions, the lack of funding sources so that the dependence on the budget from the central government is very high. In addition, cross-sectoral coordination did not go well because each agency still had sectoral ego even though transmigration affairs were not only the task of the transmigration technical service but were the affairs of the local government. Even, human resource support is still very limited, while the procurement of ASN (State Civil Apparatus) must obtain approval from the central government, so local governments are experiencing difficulties.